Addressing quality of life in the patient with interstitial cystitis/bladder pain syndrome - Vinaya Vasudevan; Robert Moldwin (Asian Journal of Urology)
Interstitial cystitis/bladder pain syndrome (IC/BPS) is a debilitating, chronic condition characterized by chronic pelvic pain, urinary urgency, and frequency and is well-known to be associated with a decrease in work productivity, emotional changes, sleep, sexual dysfunction, and mobility. Many metrics of quality of life (QoL) in this patient population have been developed; however, a unified, standardized approach to QoL in these patients has not been determined. The effects of IC/BPS and co-morbid conditions on QoL are described using current validated metrics. Next, data regarding successful treatment of IC/BPS in terms of QoL improvement are reviewed. While QoL is the single most important clinical measure of success in the treatment of patients suffering from IC/BPS, addressing QoL in this patient population remains a significant challenge, as its effects on QoL are highly variable and unable to be differentiated from the effects of comorbid conditions on QoL, including depression, poor sleep, and inability to work. Future studies will need to address treatment efficacy on the basis of IC/BPS specific QoL metrics, and multi-modal assessment and therapy to address comorbid disease will also play an important role in the future to ensure comprehensive management of these patients.